Organochlorinated pesticides in Italian women of reproductive age: Serum levels and determinants of exposure - Valentina Marra; Silvia Valentini; Annalisa Abballe; Silvia De Luca; Fabiola Ferri; Anna Rita Fulgenzi; Nicola Iacovella; Anna Maria Ingelido; Elena De Felip (Elsevier, 2023)
Background: HCB, β-HCH, DDE are the organochlorinated pesticides most frequently detected for their extreme persistence and their effects on the reproductive system. Objectives: The aim of the present study was to acquire information on the exposure of young Italian women to the most widespread organochlorinated pesticides. Methods: 549 women (20-40 years) were enrolled in six Italian regions from 2011-2013. Areas at different (presumed) exposure to persistent organic pollutants were included in all regions, such as rural, urban and industrial areas at possible incremental exposure. Results: Median concentration values were 18.2 ng/g lipid base (lb) for HCB, 6.6 ng/g lb for β-HCH and 112.9 ng/g lb for DDE. Results showed higher HCB, β-HCH and DDE levels in older women compared to the 20-29 age group. Higher levels of all the three pollutants were observed in the rural areas with respect to the urban and the industrial areas. For all of the compounds, we observed a different distribution between the Italian regions. This variability is difficult to fully understand, differences in diet and lifestyle may play a role, as well as a local use of these chemicals in the past. Conclusions: This study produces a large dataset of pesticide concentrations in Italian women.